Genotype determining low catechol-O-methyltransferase activity as a risk factor for obsessive-compulsive disorder - Karayiorgou, Maria (The National Academy of Sciences of the USA, 1997)
In the present study, we address the role of the gene for catechol-O-methyltransferase (COMT), a key modulator of dopaminergic and noradrenergic neurotransmission, in the genetic predisposition to obsessive-compulsive disorder (OCD). We show that a common functional allele of this gene, which results in a 3- to 4-fold reduction in enzyme activity, is significantly associated in a recessive manner with susceptibility to OCD, particularly in males. This association is further supported by psychiatric evaluation of patients who carry microdeletions encompassing the comt gene. The mechanism underlying this sex-selective association remains to be defined and may include a sexual dimorphism in COMT activity, although close linkage with a nearby disease susceptibility locus cannot be excluded at this point.